Histomorphology of Pancreatic Islet in Physiological Aging Female Rats Post Intravenous Human Wharton’s Jelly Mesenchymal Stem Cell Injection - wining astini (Stem Cell Research and Development Center, Universitas Airlangga, 2019)
The increasing population of aged people will have the important role in the life, but the function of their bodies will decrease because of aging. Aging will increase the risk of degenerative disease, one of example is diabetes. The disease is related to the aging in the pancreatic organ which progressively declines by age. The aimed of the experiment was to determine the effect of human wharton’s jelly mesenchymal stem cells by injecting intravenously in aging female rats. This study used 3 young female rats (3 months) and 6 aging female rats (24 months). The experiment consisted of three groups. The young control group (A), the aging control group (B) that received NaCl (0.9%) 0,4 mL, the aging treatment group (C) received 1 x 106 cells/kg of human wharton’s jelly mesenchymal stem cells 0,4 mL. The aging control and the aging treatment group were injected 4 times with the interval in 3 months. The end of the experiment (12 months), the rats were anesthetized and sacrificed. The pancreatic tissues were collected to examine the pancreatic islets by histology studies. Changes of the pancreatic islet in control and treated groups were examined using hematoxylin and eosin staining. These findings conclude that injecting human wharton’s jelly mesenchymal stem cell increase the diameter and total pancreatic islet in the treatment group. In other side, the cell population of pancreatic islet also have significant differences (P<0.05) in treated physiological aging female rat groups than control aging female rat group.